The causal relationship between obesity and skin and soft tissue infections: A two-sample Mendelian randomization study - Hu, Hongxin; Mei, Jian; Lin, Mei; Wu, Xianwei; Lin, Haibin; Chen, Guoli (Frontiers in Endocrinology, 2022)
Objective: Many observational studies have shown that obesity strongly affects the skin and soft tissue infections (SSTI). However, it is unclear whether there is causal genetic of obesity on SSTI. Methods: A two-sample Mendelian randomization (MR) study was used to explore whether obesity is causally associated with SSTI. The genome-wide statistics (GWAS) were obtained from the MRC IEU OpenGWAS database. Single nucleotide polymorphisms (SNPs) with significant genome-wide differences (P< 5×10-8) and independent (r2< 0.01) were selected for MR analysis. Inverse variance weighting (IVW) was used to assess causality, and the results were reported as ratio ratios (ORs). Subsequently, heterogeneity was tested using Cochran's Q test, pleiotropy was tested using the MR-Egger intercept, and sensitivity analysis was performed using leave-one-sensitivity rates to assess the robustness of the results. Results: The results of MR analysis showed a positive effect of obesity on SSTI, and the presence of obesity may increase the risk of SSTI by 55% (OR=1.55; 95%CI=1.42-1.71; P< 0.001). The results were reliable and stable and were confirmed by sensitivity tests. Conclusion: This study found a positive causal effect of obesity on SSTI. Reasonable weight control is a possible way to reduce the occurrence of SSTI, especially for patients with surgery.